Evaluation of previous and acquired knowledge of undergraduate dentistry students about the use, conservation and hygiene of removable prostheses and oral cavity (Research, Society and Development, 2022)
The toothless population worldwide has increased due to population growth and increased life expectancy for the elderly, making the demand for removable prostheses continue to grow. For this rehabilitative treatment of toothless patients with removable prostheses to be successful in the long term, instructions and guidance by the dental surgeon to patients regarding the care of dental prostheses are necessary. However, the literature demonstrates that users of removable prostheses do not know the correct way of cleaning and maintaining the prosthesis, since they do not receive any guidance regarding the subject from the responsible dentist. The objective of this work was to evaluate, through a questionnaire, the knowledge of the students of the Dentistry course at the Prof. Edson Antônio Velano, campus Alfenas-MG, on the use, conservation and hygiene of removable prostheses and oral cavity. We were able to conclude that the academics in the advanced group, from which they concluded the prosthesis disciplines, are able to guide patients correctly on the use, conservation and hygiene of removable prostheses and oral cavity, while the academics in the beginner group have just random information on the subject and do not have enough knowledge to guide correctly.